EVALUATION OF NUTRITIVE VALUE AND IN VITRO METHANE PRODUCTION OF FEEDSTUFFS FROM AGRICULTURAL AND FOOD INDUSTRY BY-PRODUCTS - Santoso, B.; Hariadi, B.T. (Journal of the Indonesian Tropical Animal Agriculture, 2009)
The aim of this research was to evaluate the nutrient degradability, in vitro methane (CH4) production ofseveral agricultural and food industry by-products in relation to their chemical composition. Twenty-onesamples of 7 feedstuffs from agricultural and food industry by-products consisted of corn straw, potatostraw, rice straw, cocoa pod, sago waste, rice bran, soybean curd residue were evaluated by an in vitro gasproduction and nutrient degradability. The feedstuffs varied greatly in their crude protein (CP), neutraldetergent fiber (NDF) and non-fiber carbohydrate (NFC) contents. Crude protein ranged from 1.5 to 21.8%,NDF from 31.6 to 71.1% and NFC from 1.5 to 50.8%. Among the seven feedstuffs, soybean curd residuehad the highest CP content, on the other hand it had the lowest NDF content. Dry matter (DM) and organicmatter (OM) degradability were highest (P<0.01) in soybean curd residue among the feedstuffs. The CH4production was significantly higher (P<0.01) in rice straw, cocoa pod and corn straw as compared to sagowaste. There was a strong positive correlation (r = 0.60; P<0.01) between NDF concentration and CH4production. However, the total gas productions was negatively correlated (r = -0.75; P<0.01) with NDFcontent. The CH4 production of feedstuff is influenced by NDF content.